“Home to Fail” Discharges: A Question of Motivation - Landry, Christinia (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2023)
Sending patients “home to fail” while anticipating their speedy readmittance is, prima facie, ethically troubling as are all unsafe discharges. However, “home to fail” cases may also be covertly ethically troubling insofar as they raise questions of medical paternalism due to a motivational component which drives these types of cases: by discharging a patient “home to fail” she will come to appreciate that living at home is unsafe and thus unwise, prompting her to choose differently in the future.